Complementary and alternate medicines: a forensic analysis of the potential adulteration of over-the-counter anorectics and "lifestyle" medicines in South Africa - Catterson, Sandra Lynne (Division of Forensic Medicine and Toxicology, 2018)
Background: Complementary and Alternate Medicines (CAMs) in South Africa are not yet subjected to the same rigorous testing required for allopathic (prescription) medication, yet they are freely available as over-the-counter medicines. Past research has shown the presence of a banned drug, sibutramine in natural anorectics and a schedule 6 prescription drug, sildenafil, found in natural erectile dysfunction preparations. Methods: Initially, 26 exhibits (18 erectile dysfunction medicines and 8 anorectics) were screened for active pharmaceutical ingredients using high performance liquid chromatography tandem mass spectrometry. An AB SCIEX 3200 TRAP® linear ion-trap quadrupole mass spectrometer was used to detect and subsequently quantitate these active pharmaceutical ingredients using a targeted multiple reaction monitoring mode. Samples were extracted with 50% v/v methanol in water. A method for the quantitation of sildenafil was subsequently partially validated. The intra- and inter-assay precisions were evaluated and the linearity of the method was investigated in the range of 20 ng/mL to 2000 ng/mL. The method was then successfully applied to a random selection of CAMs. A random sample (n=61) of erectile dysfunction CAMs were selected for quantitation from two different clusters. Cluster 1 comprised of supermarkets and cluster 2 of pharmacies. Results: The validation method for sildenafil showed that the limit of detection was 1.09 ng/mL and the limit of quantitation was 20 ng/mL. The correlation co-efficient and bias were less than 20%. Initial screening of the 26 exhibits indicated that sildenafil was present in 12 of the 18 samples tested and sibutramine in 6 of the 8 anorectics. Of the later 61 exhibits tested, 43 tested positive for sildenafil. The mass of sildenafil per sample ranged from 1.09 ng/mL to 123.7 mg/sample. Conclusion: The lack of label content, regulation and legislation exposes the consumer to the risk of consuming an active pharmaceutical ingredient which may very likely have an adverse effect on their health. There is a need to raise public awareness to the potential dangers of unregulated CAMs, encourage doctors to become more aware of their patients' consumption of CAMs and to motivate the Medicines Control Council to follow through with their deadlines for the regulation of CAMs.